An annotated checklist to the trees and shrubs of the Upper Katanga (D.R. Congo) - Meerts, Pierre (Phytotaxa, 2016)
A checklist to the trees and shrubs of Upper Katanga (the Zambezian part of Katanga, ca. 260,000 km²) (D.R. Congo) is presented. It comprises 694 taxa (664 species, 15 subspecies, 15 varieties). For each accepted taxon the list provides habitat and geographic distribution. Eleven taxa are new records for the D.R. Congo and 29 are new records for Upper Katanga. Fourteen new synonyms are proposed. Two families stand out as particularly species-rich, i.e. Fabaceae (110 taxa, i.e. Caesalpinioideae: 50; Faboideae: 29; Mimosoideae: 31) and Rubiaceae (74). Six genera comprise 10 taxa or more i.e. Ficus (25), Combretum (17), Monotes (17), Brachystegia (15), Diospyros (11), Acacia (11). The three most important woody vegetation types in Upper Katanga have different phytogeographic and taxonomic assemblages: miombo woodland (254 taxa, 62% of which are Zambezian, over-representation of Caesalpinioideae), riverine and swamp forest (196 taxa, 36% of which are Guineo-Congolian, 17% Afromontane), and Zambezian dry evergreen forest (117 taxa, 37% of which are Guineo-Congolian, Rubiaceae over-represented). Twenty taxa (3%) are strictly endemic to Upper Katanga, most of which occur only in the Katango-Zambian sector of the Zambezian region. Taxonomic uncertainties are emphasized including 13 endemics known by one or two collections only. Forty-nine taxa are almost exclusively associated with termite mounds. For the miombo woodlands eight ecological groups of indicator species are proposed.